Differences in verbal and nonverbal communication between depressed and non-depressed elderly patients. (2nd October 2018) - Asan, Onur; Kim, Sojung Claire; Iglar, Paul; Yan, Alice
ABSTRACT: Introduction: Doctor-patient communication is a complex process where verbal and nonverbal interactions happen simultaneously. We systematically evaluated and compared these behaviors in geriatric clinical visits with depressed and non-depressed elderly patients using communication accommodation theory (CAT). Method: A cross-sectional analysis of doctor-patient interactions during 43 videotaped primary care geriatric sessions was conducted. Twenty-one of the patients had symptoms of depression, while 22 were not depressed. These sessions originated from a subset of 70 videos from the National Institute on Aging and were obtained for the purpose of studying doctor-patient communication. Results: Our study showed that for nonverbal communication, non-depressed elderly patients had longer eye gaze at the doctor than the group of depressed patients. Doctors gazed at the chart longer while seeing depressed versus non-depressed patients. For verbal communication, treatment discussion in seconds was significantly different between depressed elderly patients (420.30 s) and non-depressed elderly patients (468.58 s). The average duration in seconds of patient talking, doctor talking, symptom discussion, and silence time, were different between the two populations. Discussion: Elderly patients with depression have different communication patterns with providers than patients without depression. Different communication strategies need to be implemented to better accommodate these patients' different needs and expectations during their clinic visits. Our findings provide practical implications for facilitating better patient-centered care by educating healthcare providers about communication accommodation strategies.